Digital arts : an introduction to new media - Hope, Cat; and Ryan, John (NewDelhi Bloomsbury, 2019)
Digital Arts presents an introduction to new media art through key debates and theories. The volume begins with the historical contexts of the digital arts, discusses contemporary forms, and concludes with current and future trends in distribution and archival processes. Considering the imperative of artists to adopt new technologies, the chapters of the book progressively present a study of the impact of the digital on art, as well as the exhibition, distribution and archiving of artworks. Alongside case studies that illustrate contemporary research in the fields of digital arts, reflections.